Policy on Formulation of Criminal Responsibility for Children in Conflict With the Law - Dedy Ananta Ginting; T. Riza Zarzani. N; Rahul Ardian Fikri (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2024)
Children are the next generation of the nation who need to receive guidance and protection to ensure their optimal physical, mental and social development. In its development, efforts to guide and protect children are often faced with problems and obstacles that ultimately lead to deviations in children's behavior. These deviations are often violations of legal norms and crimes by children. Children who are in conflict with the law must be held accountable for their actions, either through non-penal or penal processes. Regulations on child criminal acts are regulated in Law No. 11 of 2012 concerning the Juvenile Criminal Justice System. In principle, child protection is carried out based on the best considerations for children. The purpose of this study is to determine and analyze how the policy of formulating criminal responsibility for children in conflict with the law according to Law No. 11 of 2012 concerning the Juvenile Criminal Justice System; and to determine and analyze the policy of formulating criminal responsibility for children in conflict with the law in the future. This study uses a normative legal approach. The specifications of this study are descriptive analytical. The type of data in this study, namely secondary data includes primary legal materials in the form of laws and regulations and secondary legal materials in the form of book references and expert opinions. The data collection method used is the method of collecting data through literature studies. The analysis method used is qualitative analysis. The results of the study indicate that the criminal liability of children in conflict with the law according to Law No. 11 of 2012 is regarding the age limit of children who can be punished is 12 years, in the law there are also diversion efforts carried out before or even during the trial process, this is intended to minimize the punishment imposed on children (ultimum remidium). This process is carried out for the best consideration for children, because the effects of criminal law (stigmatization) are very bad for child development.